Analysis and Behavior of Double Sheet Pile Cofferdam - Bashar S. Qubain; Jianchao Li; Kamil Nuzha (Deep Foundations Institute, 2016)
"The Philadelphia Water Department is rehabilitating Belmont Raw Water Basin. As part of this work, a 500-ft long, temporary cofferdam was designed to retain 35 ft of combined water and soil at the western half during the reconstruction of the eastern half. A cofferdam that comprises two integral rows of sheet piles was selected to take advantage of the soil’s weight between the sheet piles for increased stability. To fine tune the design, a geotechnical investigation was carried out to verify the subsurface conditions and, in particular, the top of rock variations along the centerline of the cofferdam. A detailed finite element analysis was performed based on the subsurface findings and incorporating the construction sequence to evaluate the behavior of the cofferdam at the following stages: installation of tie rods to connect to the two rows of sheet piles; partial excavation and installation of tiebacks; complete excavation of the east basin, and demolition of the cofferdam. Inclinometers and survey markers were installed every 100 ft along the cofferdam and were monitored throughout construction. The deformation measurements were in good agreement with the finite element results.INTRODUCTIONThe Philadelphia Water Department (PWD) Belmont Raw Water Basin is located at the intersection of City Line and Belmont Avenues in Philadelphia, PA. The facility actually contains two raw water basins, east and west, separated by an earthen dividing dike. Water leakage at the bottom of the basins and through the dividing dike together with increasing demand for a larger storage capacity dictated the replacement of the wide earthen dike with new narrower concrete structure. The temporary cofferdam was designed for a two-year period to facilitate excavation support, water cutoff, removal of the existing earthen dike and replacing it with a new concrete dike. During this construction sequence, the water level in the west basin had to be maintained at or near its full capacity.Various excavation support systems were considered for this project prior to the selection of a double wall sheet pile cofferdam. Fig. 1 shows a plan view of the cofferdam and the new dividing dike. A typical cross section of the two structures is shown in Fig. 2. Double row sheet pile walls are commonly used as both temporary and permanent retaining systems in open water applications such as construction works, quaywalls, breakwaters and revetments for storing industrial waste as indicated by Ohori, et al. (1984), Ohori et al. (1988), and Khan, et al. (2001). There are many advantages to double row sheet pile systems as recognized by Ohori, et al. (1984; 1988): (1) It can be installed and removed in the presence of water easily and quickly; (2) it provides stability with small width to height ratio, utilizing the existing soils between the installed sheet pile rows; and (3) it serves well as a means for water cutoff. These advantages meet the specific project requirements."